CASE BASE REASONING DALAM PENUNTUTAN HUKUM BERDASAR UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK NO.11 TAHUN 2008 - , Agung Pribadi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Case base reasoning(CBR) is a searching method for a solution by find the similarity values between the old cases with new cases. The aim for CBR application in legal prosecution of law base of information and electronic transaction no.11 of 2008 is a system that used to looking for similarity over a new cases to past cases and used as public prosecutor notes (JPU) in determining claims with aim to shorten the prosecutor performance in making a reference in next court demands. The research methodology began by collection of obtained data from police such as prosecution suspects information, investigators, criminal acts, ballast, until evidence. Based on data from a suspect's age, type of measures and ballast (if it any), established the vector value angles and then calculated using cosine coefficient similarity(CCS) and error estimation(EE). Testing conducted by counting the number of vector values at the point of age, governmental or non-govermental ballast. The maximum Vector value of ages is 1, while each sub-feature weights are 0.5. Similarity values obtained were above 0.8 with estimation error under 0.08. Similarity value above 0.8 means are similar and identical approaching and error estimation under 0.08 means the results have a high-value validation. Keywords: CBR, JPU, vector, CCS, EE